(untitled) (GEOmedia, 2024)
This article covers five key benefits of Leica Geosystems monitoring solutions using cases from around the world to demonstrate how such customized systems positively impact the safety of rail operations: customized monitoring solutions equipped with best-in-class tools; automated real-time monitoring increases safety and minimizes disruptions; hybrid monitoring techniques with a range of sensors; railway model monitoring software for quick setup, centralized analysis and customized reporting; ensure continuity with LOC8.